2002
DOI: 10.1021/jm020848t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of 1-[(1,2-Diphenyl-1H-4-imidazolyl)methyl]-4-phenylpiperazines with Clozapine-Like Mixed Activities at Dopamine D2, Serotonin, and GABAAReceptors

Abstract: A series of 18 1-[(1,2-diphenyl-1H-4-imidazolyl)methyl]-4-piperazines (1a-r) were designed and synthesized as possible ligands with mixed dopamine (DA) D(2)/serotonin 5-HT(1A) affinity, with the aim of identifying novel compounds with neurochemical and pharmacological properties similar to those of clozapine. The binding profile at D(2) like, 5-HT(1A), and 5-HT(2A) receptors of title compounds was determined. Modifications made in the phenyl rings of the parent compound (1a) produced congeners endowed with a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…An in vitro study described clozapine as inhibiting GABA-evoked chloride currents at recombinant GABA A receptors [33]. In a rat study, Bragina et al [34] suggested that clozapine increases GABA activity by upregulating vesicular GABA transporters (VGAT) in the frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study described clozapine as inhibiting GABA-evoked chloride currents at recombinant GABA A receptors [33]. In a rat study, Bragina et al [34] suggested that clozapine increases GABA activity by upregulating vesicular GABA transporters (VGAT) in the frontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Among their derivatives,1 ,2-diarylimidazoles show ab road range of biological activities. [4,5] Considerable attention hast herefore been focused on the synthesis of these privileged scaffolds. [4,5] Considerable attention hast herefore been focused on the synthesis of these privileged scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been suggested that drugs enhancing the g-aminobutyric acid (GABA) transmission could be helpful in PD (5). In fact, it has been suggested that GABA A receptors contribute to modulation of the activity of mesocortical and mesolimbic dopaminergic neurons (6).…”
mentioning
confidence: 99%